A oferta das tavernas brasileiras: uma análise comparativa - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This article presents a study of case about the retails denominated as taverns in Brazil, comprehending yours offers through the analysis of yours products and services and looking for understanding of yours operations over a specific bibliographic analysis. In order to distinguish the position of five retails as possible taverns, regard this work as a way to comprehend the growing of the tavern phenomenon in Brazil and the questions about the tourism’s function for your dissemination. By means of the proposed analysis, was possible to recognize the offering of these businesses and accomplish them with new possibilities for tourism, directing this study on the consideration of theses spaces as taverns. The focus of this research is qualitative and descriptive, using of the comparative analysis from Padronov (2013) as a review method, in order to understand the brazilian’s tavern business phenomenon up to the own tavern concept. Considering the amount of taverns in national territory and the lack of better definitions, the investigation becomes a necessity.
Keywords: Tavernas brasileiras; Turismo; Oferta turística; Gastronomia; Brazilian taverns; Tourism; Touristic offering; Gastronomy; CNPQ::CIENCIAS SOCIAIS APLICADAS